Contribuições para o estudo de atribuição de responsabilidades em circuitos elétricos de baixa tensão - Reis, Paulo Henrique Ferreira dos [UNESP] (2015)
This work, aims to the study of the accountability problem focused on single-phase circuits with low voltage characteristics (low level of short circuit). In this scenario, the advancement of electronic loads and switchin devices have promoted and environment in which voltages and currents present high harmonic content, reducing the electrical power quality. In this context, the objective of this work is to study the behavior of linear and nonlinear loads and draw conclusions on accountability in electrical grids, i.e., responsibility in the harmonic content generation. For this purpose, it was applied the Conservative Power Theory (CPT) which is a mathematical tool for electrical circuits analysis on both sinusoidal and nonsinusoidal conditions. Furthermore, the CPT allows the application of a Accontability Methodology that takes into account information of the line impedance (equivalent Thévenin viewed by point of common coupling) and the equivalent parameters of the load. These two considerations represent a differential in relation to the studied methodologies. So, an electrical circuit containing linear and non-linear loads was proposed, and the Accountability Methodology was studied and discussed, seeking answers about the power portions that should be accontable to the harmonic loads. The load characterization and the impedance estimation presented satisfactory results. Then, the Accontability Methodology proposes that the fundamental active power should be accontable to the loads, since it represents the power portion that really flows the power source to the load. In addition, the work showed the fragility of PRODIST in relation to the IEEE standard concerning the harmonic voltage distortion established limits at the point of common coupling